The Personal Orientation-Perceived Organizational Climate Fit And Managerial Career Success - Ramasamy, Thevarani (2001)
Two general theories of career success dominate the generic management literature. The first, "human capital," hypothesizes that individual's assets, such as education, skill, and personal characteristics determines career success. The second theory, "organization structure," holds that there are factors built into the fabric of organizations that work either for or against the career success of an individual. This study attempted to bring together the two constructs, namely the individual and the organization, and how the right match between them determines career success for the individual.